2008
DOI: 10.2105/ajph.2007.111468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enrollment in Medicaid Versus the State Children’s Health Insurance Program on Kindergarten Children’s Untreated Dental Caries

Abstract: Untreated tooth decay continues to be a significant problem for children with public insurance coverage. Children who participated in a separate SCHIP program had fewer untreated dental caries than did children enrolled in Medicaid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Evaluation of examiner performance has demonstrated reliability and validity for these estimates, 18 and data have been used in a number of research studies. [19][20][21] For this study, the unit of analysis was the school year, and caries experience was measured as the school-level average number of dmft per screened kindergarten student.…”
Section: Outcome Variablementioning
confidence: 99%
“…Evaluation of examiner performance has demonstrated reliability and validity for these estimates, 18 and data have been used in a number of research studies. [19][20][21] For this study, the unit of analysis was the school year, and caries experience was measured as the school-level average number of dmft per screened kindergarten student.…”
Section: Outcome Variablementioning
confidence: 99%
“…Children from poor households are twice as likely to have untreated dental caries as children from higher income households (Dye et al, 2010). Furthermore, Medicaid-enrolled children are significantly more likely to have untreated caries than other children (Brickhouse et al, 2008). These factors have motivated efforts to address the ECC epidemic in socio-economically vulnerable children, in part, by ensuring access to preventive dental care.…”
mentioning
confidence: 99%
“…5 Although expansions in insurance coverage have improved access to oral health care, untreated tooth decay continues to be a significant problem, even for children with public insurance coverage. 6,7 A recent study found that children enrolled in Medicaid or the State Children's Health Insurance Program were 1.7 times more likely to have untreated dental caries than children not enrolled in one of these programs. 7 One explanation for children's oral health problems is the well-documented workforce shortage.…”
mentioning
confidence: 99%
“…6,7 A recent study found that children enrolled in Medicaid or the State Children's Health Insurance Program were 1.7 times more likely to have untreated dental caries than children not enrolled in one of these programs. 7 One explanation for children's oral health problems is the well-documented workforce shortage. 8 The current workforce of dentists in the United States is inadequate to meet the oral health care needs of children in terms of numbers of dentists, as well as their distribution, ethnicity, education, and practice orientation, and the situation may be getting worse as the dentist-to-population ratio continues to decline.…”
mentioning
confidence: 99%